Мониторинг состояния асинхронных двигателей с использованием методов токовой диагностики (SCIENCE and SOCIETY, 2025)
Nowadays, asynchronous motors (AM) are widely used in all areas of production. In order to reduce equipment costs, the development of new methods is relevant for monitoring the state of engines without stopping.